Nutrients and chlorophyll-a exchanges through an inlet of the Ria Formosa Lagoon, SW Iberia during the productive season - Unravelling the role of the driving forces - Cravo, Alexandra (2020)
Despite the advances and increase of observations of physical and chemical processes to better understand thefunctioning of coastal environments, a large gap still exists in quantifying exchanges and interactions betweenadjacent coastal systems. It is important to bear in mind that the dynamics and mass exchanges depend on thevariability of the driving mechanisms and respond to several time scales (tidal, seasonal and inter-annual). Thegeneral objective of this work was to unravel the role of the driving forces on the nutrients and chlorophyll-aexchanges at the Ancão inlet of Ria Formosa lagoon during the most productive season - spring. This is thesmallest inlet of the western system, the closest to continental interface and the one where migratory patterns areevident. So, the changes along time could be more evident there than at the other two inlets of the westernsector. Ancão inlet will serve as a reference to compare the mass budgets exchanged with the ocean with theother two inlets. Specifically, this work intends to: i) better understand the behaviour of this inlet; ii) its role inthe mass exchanges; and iii) its interplay with phytoplankton productivity during the peak season. In thiscontext, the transport of water, nutrients and chlorophyll-a(proxy of phytoplankton density) were estimatedacross the Ancão inlet section during the spring season. Surveys were conducted under extreme fortnightly tidalconditions during 2007, 2009 and 2012, covering different hydrodynamic, meteorological and environmentalconditions. To estimate the mass transport,field velocities, nutrients and chlorophyll-aconcentrations weremeasured concurrently along its cross section. Results show that although the hydrodynamic and morphologicchanges recorded at this inlet provoked a loss of hydraulic efficiency apparently these did not markedly affectthe mass exchanges during the spring productive season. Globally, the contribution and intensity of the me-teorological/physical, chemical and biological drivers superimposed those affected by tides, reflected in thedifferences between thefive surveys conducted. Upwelling was frequent during the spring season and played akey role on the exchanges and mass transport through the Ancão inlet. Data also show that nutrients behaveddissimilarly; silicate was consistently exported, nitrate mostly imported, dependent on the intensity of upwellingand biological consumption, while phosphate generally followed the direction of residual circulation.Chlorophyll-ashowed a general import except in both 2012 campaigns, when it was exported in small amounts(< 1 kg). Data support that during spring season, particularly in periods when upwelling is relevant, theavailability of nutrients on the coast will promote afterwards the growth of phytoplankton that enters andfertilizes the Ria Formosa, increasing its productivity. The estimated amounts are relative to the smallest inlet ofthe western sector of Ria Formosa. In consequence, it may be anticipated that through the other main inlets fromthis sector the exchanges are intensified and may enhance their contribution to the Ria Formosa fertilization.